Pendampingan Penyusunan Program Kerja BPD dalam Meningkatkan Akuntabilitas Desa - Haryati, Haryati; Pujiono, Pujiono; Nuswantara, Dian Anita; Yanthi, Merlyana Dwinda; Siregar, Cantika Sari (Universitas Negeri Surabaya, 2023)
Badan Permusyawaratan Desa (BPD) is a solid partner of the village government in building and prospering the people as well as the full holder and implementer of village community sovereignty and plays a role not as an extension of the government, but rather as a representative of the community as well as an intermediary between the community and the Village Government. Village management must meet the principles: (1) Legal Certainty, (2) Orderly Administration of Government, (3) Orderly Public Interest, (4) Openness, (5) Proportionality, (6) Professionalism, (7) Accountability, (8) Effectiveness and efficiency, (9) Local wisdom, (10) Diversity, and (11) Participatory. Of all the principles of village management, the principles of accountability and transparency are often not met, thereby increasing the opportunity for fraud to occur, so assistance is needed in the preparation of BPD work programs in increasing village accountability. Mentoring activities succeeded in increasing the competence of village officials in the preparation of BPD work programs to improve accountability and good transparency. This can be seen from the increasing value of the acquisition of pretest scores above 70 by 69% and posttest scores above 70 by 89%.